2021
DOI: 10.51264/inajl.v2i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Citarum River Water Pollution and Stress Responses in The Tolerant and Sensitive Fish

Abstract: Severe river pollution creates a stressful environment for aquatic organisms, causing disturbances to their health and leading to their extinction. Thus, in this study, the stress responses of tolerant (Oreochromis niloticus) and sensitive (Cyprinus carpio) fish to river pollution in the Citarum River, Indonesia were investigated. The two groups of fish were exposed to varying levels and lengths of water pollution, their blood was sampled, and stress responses were identified. The red blood cells (RBC) count, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…In regards to the formulas of Rismeyer (1998) in [22], the phosphorus load from FNC activities entering the water reservoir ranged from 393 tons y -1 to 3355 tons y -1 (Table 7). 5; 3) Inlet and outlet discharge data of reservoir often have differences because they were set for operational purposes of electricity generation); 4) Flow rate data based on the sum of the total water flow at the inlet 5) The lowest value of TP from other inlets;…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In regards to the formulas of Rismeyer (1998) in [22], the phosphorus load from FNC activities entering the water reservoir ranged from 393 tons y -1 to 3355 tons y -1 (Table 7). 5; 3) Inlet and outlet discharge data of reservoir often have differences because they were set for operational purposes of electricity generation); 4) Flow rate data based on the sum of the total water flow at the inlet 5) The lowest value of TP from other inlets;…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the river receives waste from industry, agriculture, settlements, and livestock. Some studies have shown that the water quality in most locations in the upper Citarum River was poor, and that the pollution levels far exceed the maximum allowable levels [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Padatnya daerah permukiman dan juga banyak aktivitas industri di sepanjang aliran sungai Kali Mas dapat berdampak pada masuknya bahan pencemar ke dalam badan air (Oktavia et al, 2015). Bahan pencemar tersebut dapat mencemari sungai dan menyebabkan terjadinya penurunan kualitas air, serta mengganggu kehidupan biota akuatik yang hidup di dalamnya (Sunardi et al, 2021).…”
Section: Pendahuluanunclassified
“…This is also supported by a WHO statement which states that the Citarum is the most polluted river in the world. Previous studies have found that around 40-80% of large marine debris (diameter size >20 mm) is plastic, and is associated with food and beverage products including bottles, bottle caps, bags, straws, and polystyrene pieces [7,8]. Considering the big role of the Citarum River and its impact on life, it is important to perform a monitoring method in the river regarding the occurrence of plastic.…”
Section: Introductionmentioning
confidence: 99%
“…The uniqueness of this river is that there are three consecutive reservoirs that may retain some of the debris carried by the river flow from 1062 (2022) 012024 IOP Publishing doi:10.1088/1755-1315/1062/1/012024 2 the upstream. Citarum River has a long history of pollution, and it was even named one of the top ten toxic threats in the world in 2013 [9] due to the high levels of pollution and the massive impact of pollution on the population in the Citarum River [8,10]. Fridayani [11] stated that from 2001 the government has tried to clean up the river from upstream to downstream with the various programs, the last program was named "Citarum Harum" or fragrant Citarum in order to control Citarum Watershed pollution.…”
Section: Introductionmentioning
confidence: 99%